Comparison of the 1 and 2% pilocarpine mouthwash in a xerostomic population: a randomized clinical trial - Babak Motamed; Arezoo Alaee; Arash Azizi; Hoda Jahandar; Mohammad Javad Kharazi Fard; Aryan Jafari (BMC, 2022)
Abstract Aims & background Pilocarpine is an accepted treatment for xerostomia, but limited research has been conducted on the oral, topical form. The present study aimed to compare the effects of 1 and 2% pilocarpine mouthwash on xerostomic participants. Methods In this double-blind clinical trial study, 48 subjects with xerostomia were randomly divided into three groups to measure the effects of 1 and 2% pilocarpine and placebo mouthwashes on saliva levels. The amount of saliva in the 1st and 14th days was measured at 0, 45, 60, and 75 mins, while participants used their mouthwash three times a day for 14 days. On the 1st and 14th days, they filled out the information forms on xerostomia and the medicine's side effects before and after the intervention. Results On the 1st day, the mean salivary flow at 45, 60, and 75 mins in the 2 and 1% pilocarpine mouthwash were significantly higher than in the placebo mouthwash group (p < 0.05). On the 14th day, the mean salivary flow time at 45 mins in the 2% pilocarpine mouthwash group was significantly higher than in the placebo mouthwash group (p = 0.007). Furthermore, the mean salivary flow at 60 and 75 mins in the 2% (p < 0.001) and 1% pilocarpine mouthwash (p = 0.028) was significantly higher than in the placebo group. Moreover, the salivary flow in the 2% pilocarpine mouthwash group was significantly higher than the 1% pilocarpine mouthwash (p < 0.05) during these two times. No side effects were observed in any of the subjects. Conclusions The study showed that 5 ml of 2 and 1% pilocarpine mouthwash for 2 weeks increased salivary flow in xerostomic participants compared to placebo without any side effects.